Supporting Temporal Queries on XML Keyword Search Engines - Manica, Edimar; Dorneles, Carina F.; Galante, Renata (Journal of Information and Data Management, 2010)
In this paper, we propose an approach for providing support to temporal queries on XML keyword search engines. Our proposal is based on identifying temporal constraints in a keyword query and intercepting the query processing, executed by a conventional XML search engine, in order to evaluate those constraints. Our approach allows users to find the temporal information that they are interested in without having to learn a complex query language or needing prior knowledge of the structure of the underlying data. In this paper, we present a web search log analysis, which is our main motivation for considering temporal queries in keyword search and describe the proposal that has been defined for allowing such a query. In order to demonstrate the effectiveness of our proposal, we have executed a set of experiments over three real XML datasets.